Role of ICT in Teacher Education: The Impact of ICT on Teacher Education (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Abstract – ICT is a knowledge handling, implementation and association research, technology, and engineering practice and technology management. ICT is used to treat information and its application. ICT stands for knowledge and communication technology. Information and communication technologies. In the educational environment, ICT is still commonly used. ICTs are popularly used for teachers, educators, managers and everyone interested with education. Teachers use ICT to render learning a quick and fascinating process. A professional teacher has multiple abilities and methods to instruct effectively. The growth and creation of teacher skills and expertise needs ICT and science technology expertise. In this report, we concentrated on ICT's position in education for teachers.